Stratified flow over an obstacle: a numerical experiment - Apelt, Colin James, author; Lin, Jung-Tai, author; Fluid Dynamics and Diffusion Laboratory, College of Engineering, Colorado State University, publisher (Colorado State University. Libraries, 1970)
Numerical studies of time-dependent, two-dimensional, stratified flow of incompressible, viscous, diffusive fluid are described. The particular physical problem which has been considered is that of stratified flow over a vertical fence when the motion is impulsively started from rest. Solutions have been calculated for the following two cases: Re = 397, Pr = 10, Ri = 1.58; and Re = 5000, Pr = 1, Ri = 1.58. The results are presented as contour plots of the flow variables, generated directly by the computer. A new iterative method was used for numerical integration of the governing equations and was found to be very effective. The method is based on the combination of the Crank-Nicolson method with a strongly implicit iterative method developed by Stone (1968). Full details of the method are given together with a summary of its performance on the problems calculated. It is shown that proper treatment of the inflow and outflow boundary conditions is crucial for successful numerical modeling of stratified flows.
CER69-70JTL-CJA25.
Prepared under Office of Naval Research, Contract No. N00014-68-A-0493-0001, Project No. NR 062-414/6-6-68 (Code 438), U.S. Department of Defense, Washington, D.C.
January 1970.
Keywords: Fluid dynamics; Numerical calculations; Iterative methods (Mathematics); Mountain wave